A randomized comparison of the three Papanicolaou smear collection methods [RANDOMISIERTER VERGLEICH VON DREI METHODEN ZUR ENTNAHME VON PAPANICOLAOU-ABSTRICHEN] - (:unkn) unknown (My University, 1995)
The purpose of this study was to compare the effectiveness of three cervical smear sampling devices for obtaining acceptable yields of endocervical cells in Papanicolaou smears. In a randomized, controlled clinical trial, we collected 346 smears over a 6 month period, 110 with the Cervex brush, 125 with the cotton swab plus Ayre spatula and 111 with the Cytobrush plus Ayre spatula. The cytopathology laboratory did not know the employed method and screened the smears using the Bethesda system guidelines. Statistical analysis was performed using the Pearson χ2 and analysis of variance tests. There was an increased detection of endocervical cells in the Cytobrush plus Ayre spatula and the Cervex brush groups, compared with the cotton swab plus Ayre spatula group (p = 2.39 x 10-6, p = 4.49 x 10-7 respectively). There was no statistically significant difference between the Cytobrush-spatula and Cervex brush groups (p = 0.0779). The Cytobrush - Ayre spatula and the Cervex brush sampling methods were equally effective in obtaining endocervical cells for Papanicolaou smears.
Keywords: Ayre spatula; Cervex brush; Cotton swab; Cytobrush; Papanicolaou smear